Transit timing observations from kepler. II. confirmation of two multiplanet systems via a non-parametric correlation analysis - Ford, Eric B.; Fabrycky, Daniel C.; Steffen, Jason H.; Carter, Joshua A.; Fressin, Francois; Holman, Matthew J.; Lissauer, Jack J.; Moorhead, Althea V.; Morehead, Robert C.; Ragozzine, Darin; Rowe, Jason F.; Welsh, William F.; et al. (The Astrophysical Journal, 2012)
We present a new method for confirming transiting planets based on the combination of transit timing variations (TTVs) and dynamical stability. Correlated TTVs provide evidence that the pair of bodies is in the same physical system. Orbital stability provides upper limits for the masses of the transiting companions that are in the planetary regime. This paper describes a non-parametric technique for quantifying the statistical significance of TTVs based on the correlation of two TTV data sets. We apply this method to an analysis of the TTVs of two stars with multiple transiting planet candidates identified by Kepler. We confirm four transiting planets in two multiple-planet systems based on their TTVs and the constraints imposed by dynamical stability. An additional three candidates in these same systems are not confirmed as planets, but are likely to be validated as real planets once further observations and analyses are possible. If all were confirmed, these systems would be near 4:6:9 and 2:4:6:9 period commensurabilities. Our results demonstrate that TTVs provide a powerful tool for confirming transiting planets, including low-mass planets and planets around faint stars for which Doppler follow-up is not practical with existing facilities. Continued Kepler observations will dramatically improve the constraints on the planet masses and orbits and provide sensitivity for detecting additional non-transiting planets. If Kepler observations were extended to eight years, then a similar analysis could likely confirm systems with multiple closely spaced, small transiting planets in or near the habitable zone of solar-type stars. © 2012. The American Astronomical Society. All rights reserved.
73 citations (Crossref) [2023-10-31] Citation Key Alias: pop00013 tex.type: [object Object]
Keywords: dept.phy; planetary systems; planets and satellites: detection; planets and satellites: dynamical evolution and stability; stars: individual (KIC 3231341; 11512246; KOI 168; 1102; Kepler-23; Kepler-24); techniques: miscellaneous

Characteristics of kepler planetary candidates based on the first data set - Borucki, William J.; Koch, David G.; Basri, Gibor; Batalha, Natalie M.; Boss, Alan P.; Brown, Timothy M.; Caldwell, Douglas A.; Christensen-Dalsgaard, Jørgen; Cochran, William D.; DeVore, Edna; Dunham, Edward W.; Dupree, Andrea K.; et al. (The Astrophysical Journal, 2011)
In the spring of 2009, the Kepler Mission commenced high-precision photometry on nearly 156,000 stars to determine the frequency and characteristics of small exoplanets, conduct a guest observer program, and obtain asteroseismic data on a wide variety of stars. On 2010 June 15, the Kepler Mission released most of the data from the first quarter of observations. At the time of this data release, 705 stars from this first data set have exoplanet candidates with sizes from as small as that of Earth to larger than that of Jupiter. Here we give the identity and characteristics of 305 released stars with planetary candidates. Data for the remaining 400 stars with planetary candidates will be released in 2011 February. More than half the candidates on the released list have radii less than half that of Jupiter. Five candidates are present in and near the habitable zone; two near super-Earth size, and three bracketing the size of Jupiter. The released stars also include five possible multi-planet systems. One of these has two Neptune-size (2.3 and 2.5 Earth radius) candidates with near-resonant periods. © 2011. The American Astronomical Society.
282 citations (Crossref) [2023-10-31] Citation Key Alias: pop00003 tex.type: [object Object]
Keywords: Planets and satellites: detection; Surveys; dept.phy

Characteristics of planetary candidates observed by Kepler II : Analysis of the first four months of data - Borucki, William J.; Koch, David G.; Basri, Gibor; Batalha, Natalie M.; Brown, Timothy M.; Bryson, Stephen T.; Caldwell, Douglas A.; Christensen-Dalsgaard, Jørgen; Cochran, William D.; DeVore, Edna; Dunham, Edward W.; Gautier, Thomas N.; et al. (The Astrophysical Journal, 2011)
On 2011 February 1 the Kepler mission released data for 156,453 stars observed from the beginning of the science observations on 2009 May 2 through September 16. There are 1235 planetary candidates with transit-like signatures detected in this period. These are associated with 997 host stars. Distributions of the characteristics of the planetary candidates are separated into five class sizes: 68 candidates of approximately Earth-size (Rp < 1.25 R⊕), 288 super-Earth-size (1.25 R⊕ ≤ R p < 2 R⊕), 662 Neptune-size (2 R ⊕ ≤ Rp < 6 R⊕), 165 Jupiter-size (6 R⊕ ≤ Rp < 15 R ⊕), and 19 up to twice the size of Jupiter (15 R ⊕ ≤ Rp < 22 R⊕). In the temperature range appropriate for the habitable zone, 54 candidates are found with sizes ranging from Earth-size to larger than that of Jupiter. Six are less than twice the size of the Earth. Over 74% of the planetary candidates are smaller than Neptune. The observed number versus size distribution of planetary candidates increases to a peak at two to three times the Earth-size and then declines inversely proportional to the area of the candidate. Our current best estimates of the intrinsic frequencies of planetary candidates, after correcting for geometric and sensitivity biases, are 5% for Earth-size candidates, 8% for super-Earth-size candidates, 18% for Neptune-size candidates, 2% for Jupiter-size candidates, and 0.1% for very large candidates; a total of 0.34 candidates per star. Multi-candidate, transiting systems are frequent; 17% of the host stars have multi-candidate systems, and 34% of all the candidates are part of multi-candidate systems. © 2011. The American Astronomical Society. All rights reserved.
799 citations (Crossref) [2023-10-31] Citation Key Alias: pop00002 tex.type: [object Object]
Keywords: dept.phy; planetary systems; planets and satellites: detection; stars: statistics; surveys